2016
DOI: 10.1371/journal.pone.0159096
|View full text |Cite
|
Sign up to set email alerts
|

Foraging Behaviour in Magellanic Woodpeckers Is Consistent with a Multi-Scale Assessment of Tree Quality

Abstract: Theoretical models predict that animals should make foraging decisions after assessing the quality of available habitat, but most models fail to consider the spatio-temporal scales at which animals perceive habitat availability. We tested three foraging strategies that explain how Magellanic woodpeckers (Campephilus magellanicus) assess the relative quality of trees: 1) Woodpeckers with local knowledge select trees based on the available trees in the immediate vicinity. 2) Woodpeckers lacking local knowledge s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 78 publications
(98 reference statements)
1
19
0
Order By: Relevance
“…Unlike saproxylic insects, woodpeckers foraged more on girdled trees in the clustered treatments than uniform treatments. Foraging decisions may be based on information gathered across multiple spatiotemporal scales, as demonstrated for the Magellanic Woodpecker (Campephilus magellanicus King [42]). Indeed, this species acts as a locally informed forager and uses visual clues from the immediate vicinity to select individual trees, whereas the time spent to forage on the same tree is rather influenced by their long-time memory of tree availability along the foraging route or within their home range and tree-level attributes (e.g., DBH, decay stage).…”
Section: Differences Between Snag-supply Treatmentsmentioning
confidence: 99%
“…Unlike saproxylic insects, woodpeckers foraged more on girdled trees in the clustered treatments than uniform treatments. Foraging decisions may be based on information gathered across multiple spatiotemporal scales, as demonstrated for the Magellanic Woodpecker (Campephilus magellanicus King [42]). Indeed, this species acts as a locally informed forager and uses visual clues from the immediate vicinity to select individual trees, whereas the time spent to forage on the same tree is rather influenced by their long-time memory of tree availability along the foraging route or within their home range and tree-level attributes (e.g., DBH, decay stage).…”
Section: Differences Between Snag-supply Treatmentsmentioning
confidence: 99%
“…Sampling points were randomly established in stands of different forest types (Table 1), at least 100 m from the stand edge. Because adult Magellanic Woodpeckers are conspicuous, noisy (e.g., Vergara et al 2016), and thus easily detected, we recorded all woodpeckers seen and heard within 100-m-radius (e.g., Ralph et al 1993). A single trained observer annually visited each point up to eight times between 1995 and 1998, and three to five times between November and March 2016.…”
Section: Abundance Surveysmentioning
confidence: 99%
“…PSRI uses red and green bands to measure chlorophyll degradation and carotenoid content of the tree canopy, with higher values indicating more advanced decay stage of trees (e.g., see . Previous studies have demonstrated that Magellanic Woodpeckers select individual trees based on their PRSI values (see details in Vergara et al 2016). These tree preferences are consistent with the occurrence pattern of the long-horned beetle Microplophorus magellanicus, one of the main prey of woodpeckers, which respond positively to tree senescence (Vergara et al 2017).…”
Section: Habitat Variablesmentioning
confidence: 99%
“…To our knowledge, no published study has assessed potential woodpecker excavation depth, nor identified from where in the tree structure larvae are extracted, nor which species are available for consumption. Albeit, recent research exists on their habitat selection (e.g., Vergara et al 2016, Soto et al 2017.…”
Section: Introductionmentioning
confidence: 99%